REGN-COV2 antibody cocktail in patients with SARS-CoV-2: Observational study from a single institution in Japan. Issue 7 (July 2022) - Sakurai, Ayana; Marshall, Shoko; Ogasawara, Tomoko; Ogasawara, Toshie; Aoka, Yoshikazu; Sakura, Hiroshi; Uchigata, Yasuko; Ogawa, Tetsuya
Abstract: Introduction: A new treatment for coronavirus disease (COVID-19), REGN-COV2, a cocktail consisting of two neutralizing antibodies against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has been approved for patients at a risk of developing more severe disease. Methods: We retrospectively reviewed patients recently diagnosed with COVID-19 with risk factors for severe infection, who were treated with the REGN-COV2 antibody cocktail between July and September 2021. The REGN-COV2 antibody cocktail was administered to patients within 7 days of disease onset, with an oxygen saturation of >93%, and with at least one comorbidity. We investigated the percentage of patients with COVID-19-related hospitalization or death, the duration of symptoms after treatment, and the adverse effects of treatment. Results: A total of 108 patients were reviewed. Of them, 64% were aged ≥50 years, 31% had obesity, 36% had hypertension, and 18% had diabetes. In addition, 49% had multiple risk factors for severe COVID-19. Overall, 12 patients (11%) needed COVID-19-related hospitalization. No adverse effects of treatment were observed. Conclusions: This study shows that treatment with the REGN-COV2 antibody cocktail is safe and beneficial in patients at a risk of developing severe COVID-19.